Therapeutic Effects of BCG Vaccination on Type 1 Diabetes Mellitus: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Yu-Chen Chang; Chien-Ju Lin; Yu-Hsuan Hsiao; Yu-Han Chang; Shu-Jung Liu; Hsin-Yin Hsu (Journal of Diabetes Research)
Background. Type 1 diabetes mellitus (T1DM) causes the irreversible destruction of pancreatic beta cells. The Bacillus Calmette–Guerin (BCG) vaccine can modulate the immune response and decelerate disease progression. The aim of this study is to investigate the efficacy of the BCG vaccine for the treatment of T1DM. Objective. Six databases were systematically searched from inception to the end of August 2019. The randomized controlled trials (RCTs) that evaluated glycemic control in response to the BCG vaccine for T1DM were enrolled. The primary outcome was glycated hemoglobin (HbA1c) level, and secondary outcomes included fasting and stimulated C-peptide level, daily insulin dosage, and clinical remission. The revised Cochrane risk of bias tool was used for quality assessment, and meta-analyses were conducted to evaluate the efficacy of the BCG vaccine. Results. Four studies with a total of 198 subjects were included. The results of HbA1c and fasting C-peptide levels were extracted for further quantitative assessment. The pooled meta-analysis demonstrated no significant difference in HbA1c levels (mean difference [MD], −0.12; 95% confidence interval [CI], −0.53 to 0.30; I2=56%) or fasting C-peptide levels (MD, −0.15; 95% CI, −0.35 to 0.06; I2=0%) in the BCG intervention group as compared with that in the placebo group. Conclusions. There is no robust evidence to support the use of the BCG vaccine for the treatment of T1DM although the HbA1c levels tended to improve. Additional RCTs to assess the long-term effects of the BCG vaccine on glycemic control are warranted.